2012
DOI: 10.2214/ajr.11.7517
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Real-Time Strain Elastography, Transient Elastography, and Aspartate-to-Platelet Ratio Index in the Assessment of Fibrosis in Chronic Hepatitis C

Abstract: Transient elastography, real-time strain elastography, and aspartate-to-platelet ratio index values were correlated with histologic stages of fibrosis. Transient elastography offered excellent diagnostic performance in assessing severe fibrosis and cirrhosis. Real-time elastography does not yet have the potential to substitute for transient elastography in the assessment of liver fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 35 publications
1
56
0
Order By: Relevance
“…The maximum and minimum lengths of the ROI measured in our previous study were 1.90 6 0.12 (range, 1.5-2.0) and 0.90 6 0.11 (range, 0.6-1.0) cm for the liver and spleen parenchyma, and 0.44 6 0.07 (range, 0.3-0.5) and 0.28 6 0.01 (range, 0.2-0.3) cm for small vessels. 2 We also previously found that interobserver agreement in determining fibrosis stage at different liver sites and the elastic ratio calculated by the two examiners closely correlated, and did not significantly differ. 3 This evidence indicated that a small variation in the size of the ROI would not affect the value of the elastic ratio determined using real-time tissue elastography.…”
Section: Replymentioning
confidence: 52%
See 1 more Smart Citation
“…The maximum and minimum lengths of the ROI measured in our previous study were 1.90 6 0.12 (range, 1.5-2.0) and 0.90 6 0.11 (range, 0.6-1.0) cm for the liver and spleen parenchyma, and 0.44 6 0.07 (range, 0.3-0.5) and 0.28 6 0.01 (range, 0.2-0.3) cm for small vessels. 2 We also previously found that interobserver agreement in determining fibrosis stage at different liver sites and the elastic ratio calculated by the two examiners closely correlated, and did not significantly differ. 3 This evidence indicated that a small variation in the size of the ROI would not affect the value of the elastic ratio determined using real-time tissue elastography.…”
Section: Replymentioning
confidence: 52%
“…2,3 The area of the ROI placed on both the liver and the spleen parenchyma was within 2 Â 1 cm. The size of the ROI in the small vessels was usually within 0.3 Â 0.5 cm.…”
Section: Replymentioning
confidence: 99%
“…As in the case of the transient elastography (Fibroscan), shear wave elastography is difficult to perform in patients with significant obesity. Several studies have confirmed the high diagnostic efficacy of the SWE method and compliance of the results of the biopsy, TE and FibroTest [18,19].…”
Section: Shear-wave Elastographymentioning
confidence: 80%
“…In order to obtain LFI, the color map was coded from 0 (blue) to 255 (red). Then, a few parameters were calculated: mean, [12]. The ROI is placed at least 1 cm under the liver capsule.…”
Section: Fujimoto Et Almentioning
confidence: 99%